Binding of phosphorylated histone H1 to DNA. - Knippers, R (1978)
A chromatin associated protein kinase was used to add 3 moles of phosphate to seryl side chains of 1 mole of histone H1. The DNA binding properties of this in vitro phosphorylated H1 were compared with those of unmodified H1. Considerably more radioactive superhelical DNA was retained on nitrocellulose filters at 20mM-40mM NaCl by phosphorylated H1 than by unmodified H1. However, zone velocity sedimentation analysis of histone-DNA complexes indicated that similar amounts of phosphorylated and unmodified H1 are bound to DNA. It is therefore concluded that phosphorylated H1 binds distributively to many or all DNA molecules available (depending on the histone/DNA ratio) while unmodified H1 binds cooperatively to a fraction of the DNA molecules in the reaction mixture.